Narcissistic parenting in an insecure world : a history of parenting culture 1920s to present - Hendrick, Harry (Policy Press, 2016)
Harry Hendrick shows how broader social changes, including neoliberalism, feminism, the collapse of the socialdemocratic ideal, and the 'new behaviourism', have led to the rise of the anxious and narcissistic parent, In this provocative history of parenting.